Early-life famine exposure and subsequent risk of chronic disease comorbidity in later adulthood: the role of social activities - Zhao, Rui; Zheng, Qi; Chen, Le-qin; Feng, Qiang (Frontiers in Nutrition, 2025)
BackgroundWith the global population aging, the burden of health issues has shifted from infectious diseases to chronic diseases. Research indicates a significant link between exposure to famine in early life and chronic diseases. However, evidence regarding the relationships among early-life famine exposure, social activities, and chronic disease comorbidities is lacking.ObjectivesWe aimed to systematically assess how early-life famine exposure influences the risk of chronic disease comorbidities in later adulthood and how social activities modulate this risk.MethodsIn this nationwide study, we utilized data from the fourth wave of the CHARLS conducted in 2018. We included 6,641 participants and categorized them into five groups based on birth dates. We used the LCA model to reclassify the 14 chronic diseases from the CHARLS survey as the main outcome indicators. We employed stepwise logistic regression to examine the link between early-life famine exposure and the subsequent risk of chronic disease comorbidity in adulthood, presenting the findings as ORs and 95% CIs. We conducted subgroup analyses according to baseline characteristics to examine the robustness and potential differences in outcomes for chronic disease comorbidity. We evaluated the interaction between famine exposure and social engagement on both additive and multiplicative scales using generalized linear models (GLM).ResultsThe prevalence of chronic disease comorbidity patterns between 1.3% (cancer-related disease) and 19.9% (cardiovascular disease comorbidity). Those who experience famine in early life face a heightened risk of cardiovascular disease comorbidity in late adulthood, with an OR (95% CI) of 1.42 (1.12 to 1.80), urinary system disease with an OR (95% CI) of 1.87 (1.05 to 3.34), and multimorbidity with an OR (95% CI) of 1.39 (1.07 to 1.79) compared to those who did not experience such conditions. Participating in social activities can lower the risk of metabolic disease comorbidities in late adulthood for infants who experienced famine, with an (OR [95% CI] of 0.64 [0.43 to 0.97]). There was an interactive effect on the additive (OR [95% CI] of −0.42 [−2.52 to −0.32], P < 0.01) and multiplicative (P = 0.001) effect between infants with famine exposure and social activity.ConclusionExperiencing famine in early life is associated with a heightened risk of chronic disease comorbidities in later adulthood, a relationship modulated by participation in social activities. Social activities and early life exposure to famine have an interactive effect on chronic disease comorbidities in later adulthood.